From my skin to your skin: Virtual image of a hand of different skin color influences movement duration of the real hand in Black and White individuals and influences racial bias - Ambron, Elisabetta; Goldstein, Shayna; Miller, Alexander; Hamilton, Roy H.; Coslett, H. Branch (Frontiers in Virtual Reality, 2022)
Virtual reality (VR) allows individuals to experience someone else’s body, but the possible effects of this embodiment on attitudes and biases are not fully understood. Using a virtual reality (VR) task, we had previously shown that changes in the visual image of the hand influenced action: when the visual image of one’s hand was spatially displaced, participants acted as if the virtual hand was theirs. Here we tested whether these effects vary depending on the match between the skin color of the individual and the virtual hand. Black and White participants performed reaching movements with dark or light hands of naturalistic skin tones, or purple hands. As in our previous work, the correspondence between the location of the real and virtual hands was systematically varied. Both Black and White participants showed changes in the temporal and spatial parameters of the movements with the virtual hand of different colors indicating that the hand had been embodied. A larger effect of the illusion was observed in Black as compared to White individuals when performing the action with a dark-skin virtual hand. Ownership of the virtual hand that matched the participants’ skin color was associated with their explicit attitude towards their in-group in Black participants and with empathic abilities in White individuals. Importantly, performing the task with a dark-skin hand reduced the implicit racial bias of White individuals. These data show that body representation is malleable and influenced by online perceptual factors as well as attitudes and biases. Our findings raise the possibility that altering the representation of one’s body may be used to change participants’ perspectives regarding social issues.